Effect of psychotic symptoms on cognitive impairment in patients with bipolar disorder - Achalia, Rashmin Mansukh (Ind Psychiatry J, 2019)
BACKGROUND: A considerable proportion of patients with bipolar disorder (BD) have psychotic symptoms during the illness. This subset of BD due to its genetic susceptibility and family segregation has considerable overlap with schizophrenia. However, the extent to which BD patients with psychotic symptoms and without psychotic symptoms differ on neurocognitive functions is still not completely clear. AIM: The aim of this study was to examine the neurocognitive functions in BD patients with psychotic symptoms and BD without psychotic symptoms in comparison with healthy volunteers (HVs). MATERIALS AND METHODS: Thirty patients with Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition BD (16 with psychotic symptoms) and thirty age- and sex-matched HVs were recruited in the study. Clinical severity was assessed using structured rating scales. The presence of psychotic symptoms was assessed using the Lifetime Dimensions of Psychosis Scale (LDPS). All patients underwent tests, namely continuous performance test, Stroop Word-Color interference test, and Wisconsin Card Sorting Test, to measure executive functions. Differences between groups were examined using analysis of covariance with age and sex as covariates. RESULTS: There was a significant difference between groups on the performance of all the three tests, with patients performing poorer than HVs. While the HVs differed from both BD with psychotic symptoms and without psychotic symptoms, there was no difference between BD patients with and without psychotic symptoms. There was no significant correlation between LDPS score and scores on neurocognitive tests. CONCLUSION: The study findings, at least with respect to cognitive function, suggest that BD with psychotic symptoms may not be a categorically distinct subtype of BD. Cognitive functions need to be assessed in all patients with BD, regardless of psychotic symptoms, and remediation interventions need to be provided.